2018
DOI: 10.1055/s-0038-1675224
|View full text |Cite
|
Sign up to set email alerts
|

Torsion Does Not Affect Early Vein Graft Patency in the Rat Femoral Artery Model

Abstract: Background Torsion of vein grafts is a commonly cited reason for graft failure in clinical setting. Many microsurgery training courses have incorporated vein graft procedures in their curricula, and vein graft torsion is a common technical error made by the surgeons in these courses. To improve our understanding of the clinical reproducibility of practicing vein graft procedures in microsurgery training courses, this study aims to determine if torsion can lead to early vein graft failure in nonsurvival surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Past literature often reported a high patency rate of up to 100% upon applying various technical errors, given the seeming discrepancy between experimental models and clinical practice. 3 4 5 6 7 8 9 10 11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past literature often reported a high patency rate of up to 100% upon applying various technical errors, given the seeming discrepancy between experimental models and clinical practice. 3 4 5 6 7 8 9 10 11…”
Section: Discussionmentioning
confidence: 99%
“…Past literature often reported a high patency rate of up to 100% upon applying various technical errors, given the seeming discrepancy between experimental models and clinical practice. [3][4][5][6][7][8][9][10][11] In a microsurgery training setting, suture anastomosis is often the domain with the steepest learning curve, leading to patency failure ultimately when first beginning the training. A competent proficiency to reach anastomosis patency may take over 10 times of attempts and practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dispersion was observed in a previous study of ours that investigated the effect of torsion on interpositional vein graft patency. 17 Another example is that in clinical AVF procedures, a venous end to arterial side anastomosis is typically performed. 9 Since veins are thinner and more fragile than arteries, they may be more susceptible to thrombosis after being twisted.…”
Section: Discussionmentioning
confidence: 99%
“…In depth analyses of several error types, including vessel torsion and large or uneven bites has found that vessels may tolerate these imperfections along the suture line. [8][9][10] Nevertheless, while rat femoral vessel anastomoses may survive imprecise suturing technique, human anastomoses may not be as tolerant of technical errors. Additionally, these mistakes were evaluated on rat femoral arteries and veins, which while similar to human vessels, have not been fully evaluated.…”
mentioning
confidence: 99%